Commercial Disputes Resolution In The 90’s - Lymington, The Rt Hon The Lord Donaldson of (Journal of Malaysian and Comparative Law, 1992)
Text of the Seventh Sultan Azlan Shah Law Lecture (organised by the Faculty of Law, University of Malaya and the British Council) delivered by the Rt. Hon. The Lord Donaldson of Lynington on December 17, 1992 in the presence of His Majesty, Sultan Azlan Shah, the Yang di-Pertuan Agong.